Post-Conflict Aid, Real Exchange Rate Adjustment, And Catch-Up Growth - Schmidt-Hebbel, Klaus, 1955- 1955- (The World Bank, 2007)
Post-conflict countries receive substantial aid flows after the start of peace. While post-conflict countries' capacity to absorb aid (that is, the quality of their policies and institutions) is built up only gradually after the onset of peace, the evidence suggests that aid tends to peak immediately after peace is attained and decline thereafter. Aid composition broadly reflects post-conflict priorities, with large parts of aid financing social expenditure and infrastructure investment. Aid has significant short-term effects on the real exchange rate (RER), as inferred from the behavior of RER in the world. While moderate RER overvaluation is observed in post-conflicts, it cannot be traced down to the aid flows. The empirical evidence on world growth reveals new findings about the pattern of catch-up growth during post-conflicts and the role of key growth determinants on post-conflict growth. Aid is an important determinant of growth, both generally and more strongly during post-conflict periods. Because RER misalignment reduces growth, RER overvaluation during post-conflicts reduces catch-up growth. Aid and RER overvaluation combined also lower growth. But the negative growth effect of RER overvaluation declines with financial development